Metabolizable energy in energy food for growing pigs and cross-validation regression models (Revista Ciência Agronômica, 2023)
The present study aimed to determine the apparent metabolizable energy (AME) of six corn cultivars, twosorghum cultivars and two wheat brans and to evaluate the cross-validation of predictive models of AME for corn, sorghumand wheat bran for growing pigs, as estimated from the data of chemical composition. Forty-four pigs, with an average initialweight of 24.3 kg, were distributed in a randomized block design, with 11 treatments (ten food treatments and the referencediet), four replicates and one pig per experimental unit. The reference diet was replaced by 30% for the ground corn andsorghum conditions and 20% for the wheat bran condition. The values of AME for corn, sorghum and wheat meal for pigsranged from 3161 to 3275, 3317 to 3457 and 2767 to 2842 kcal kg-1 as a feed basis, respectively. The average metabolizabilityof the gross energy did not differ between the corn and sorghum cultivars, which formed a homogeneous group of food.Next, linear regression models were fitted to the 1st degree of the observed values as a function of the predicted AME, to testthe hypothesis β0= 0 and β1= 1 in an experimental sample and 200 bootstrap samples. Fourteen predictive models had lowpercentages of cross-validation, ranging from 0-29.5%. The AME1A= 2.547 + 0.969ADE model was validated in experimentalsample and 68% of bootstrap samples, proving its accuracy in estimating the AME of corn and sorghum from national data forgrowing pigs.